3D-Metal Complexes Derived from Proton Pump Inhibitors-Synthesis, Characterization and Biological Studies. Issue 4 (2012) - Malik, Suman; Das, Supriya; Singh, Archana; Mitu, Liviu
Abstract : Complexes of lansoprazole 2[[[[3-methyl, 4-(2′, 2′, 2′-trifluoro-ethoxy)]-2-pyridinyl] methyl]sulfonyl]–1 H –benzimidazole (LAN) with chlorides of Co(II), Ni(II), Cu(II), Mn(II) and Zn(II) were synthesized. LAN is a weak base and it can form several complexes with transition and non-transition metal ions. It should be noticed that the reaction of all the metal salts yielded bis(ligand) complexes of the general formula [ML2 (H2 O)2 ] and [ML2 ] (M = Co, Ni, Cu, Mn and Zn). The complexes were characterized by elemental analysis, molar conductivity, magnetic susceptibility measurements, IR, 1 H-NMR, UV-visible spectral studies, ESR, SEM, x-ray diffraction, TGA and mass spectra. In all the complexes ligand is coordinated by participation of the pyridine nitrogen of the benzimidazole ring and sulphonyl group. Electronic spectra and magnetic susceptibility reveal octahedral geometry for Mn(II), Co(II), Ni(II) and Cu(II) complexes and tetrahedral for Zn(II) complex. The antimicrobial activity of the ligand and its complexes against bacteria Pseudomonas aeruginosa, Staphylococcus aureus and fungi Aspergillus niger and Aspergillus flavous were investigated. The effect of metals on the antimicrobial activity of the ligand has been discussed.